Saberes e práticas de educação em saúde dos profissionais da atenção primária de um município de pequeno porte do estado do Ceará - Silva, Antonia Cinthya Gomes da (2022)
The development of health education is characterized as a possibility of sharing knowledge and strengthening practices, as it is an integral part of the attributions of Primary Health Care (PHC) professionals, since the development of educational actions is inherent to their work process that may interfere with the health-disease process of the population. This study aimed to understand how knowledge and health education practices are developed by Family Health Strategy professionals in a small municipality in the State of Ceará. This is a descriptive, crosssectional study with a qualitative approach. The study was carried out in a small municipality in Ceará and 27 professionals belonging to the 7 Family Health Teams in the municipality participated in the research. Data collection took place with an interview with the participating professionals, the application of a virtual form, notes in a field diary and audio recording. The descriptive corpus of speech data followed the steps of transcription and analysis using the technique of content analysis of the textual material. Regarding the concept of health education, it was associated with knowledge, awareness and education, health promotion, guidance on health and disease prevention, self-care, clarifying doubts, understanding to have access to health means, encouraging participation in programs, technologies and instruments. The practice of health education takes place in home visits and lectures held at the unit, pamphlets, during service and consultations, in the waiting room, in encouraging participation in programs developed by the Family Health Strategy (ESF), campaigns, conversations and groups. It was also commented on the motivations, the challenges, how they face them, the facilitating aspects and the themes worked on. Regarding the effects of the practice of health education, the professionals answered that some users show little participation and interaction during the activity. At the same time, other users maintain a bond of trust and dialogue with the network's professionals, which favors awareness and guidance for improving health care in primary care. Thus, this study concludes that health education is developed in different ways by most professionals, either with specific actions or in the daily routine of care at the health unit.